To solve the system of equations using multiplication, we can multiply both equations by a constant to eliminate a variable.
Let's start with the second equation:
-2x + 4y = 30
If we multiply this equation by 2, we can eliminate x:
(2)(-2x + 4y) = (2)(30)
-4x + 8y = 60
Now we have:
4x - 6y = -48
-4x + 8y = 60
Adding these two equations together:
(4x - 6y) + (-4x + 8y) = -48 + 60
2y = 12
y = 6
Now, we can substitute this value of y back into one of the original equations to solve for x. Let's use the first equation:
4x - 6(6) = -48
4x - 36 = -48
4x = -48 + 36
4x = -12
x = -12/4
x = -3
Therefore, the solution to the system of equations is x = -3 and y = 6.
Solve the system of equations using with multiplication
4x-6y=-48
-2x+4y=30
1 answer